BIOLOGY OF SPODOPTERA LITURA F. ON COLOCASIA ESCULENTA - PANSAREE, SURAJ; SHAW, S. S.; GANGULY, JAYALAXMI (Annals of Agricultural Research, 2014)
The life cycle of Spodoptera litura F. was completed in shorter period on KCA-1 genotype. The larval, pre-pupal and pupal period were also shorter in KCA-1. The weight and size of larvae and pupae was highest in KCA-1. Similarly, the larval survival, percentage pupation and adult emergence was maximum in KCA-1 as compared to other tested genotype indicating the preference of KCA-1 by Spodoptera litura whereas, the genotype Panch Mukhi was found to be the least preferred genotype by Spodoptera litura among the four tested genotypes of Colocasia esculenta.